Chronic Traumatic Encephalopathy as a Preventable Environmental Disease - Buckland, Michael E.; Affleck, Andrew J.; Pearce, Alan J.; Suter, Catherine M. (Frontiers in Neurology, 2022)
In this Perspective we explore the evolution of our understanding of chronic traumatic encephalopathy (CTE) and its relationship with repetitive head injury. As with many neurodegenerative conditions, there is an imperfect correspondence between neuropathology and clinical phenotype, but unlike other neurodegenerative diseases, CTE has a discrete and easily modifiable risk factor: exposure to repetitive head injury. Consequently, evaluation of the evidence regarding exposure to repetitive head injury and CTE risk should be undertaken using public or occupational health frameworks of medical knowledge. The current debate over the existence of CTE as a disease of concern is fuelled in part by immediate medico-legal considerations, and the involvement of high-profile athletes with inevitable media interest. Moving beyond this debate has significant potential to address and reduce disease impact in the near future, and provide novel insights into mechanisms underlying abnormal protein accumulation in CTE and other neurodegenerative diseases.